On gasifier cookstove operation fuelled by different lignocellulosic biomass materials / Shaharin Anwar Sulaiman and Nurul Aisyah Mohd Zin - Sulaiman, Shaharin Anwar; Mohd Zin, Nurul Aisyah (Faculty of Mechanical Engineering (FKM) and UiTM Press, 2014)
Gasifier based cookstoves are relatively clean and environmental friendly than that of direct combustion type. Though a few commercial designs are available, their capability in handling different biomass has not been known. The objective of this work was to characterize the basic operating properties of a gasifierbased biomass cookstove using different types of biomass fuels. The main characteristics evaluated were the efficiency of the stove. The biomass considered were oil palm fronds, dry leaves and pressed sugarcane. The efficiency of the stove was tested using standard boiling tests for 2.5 kg of water. The performance of each fuel was studied by analyzing the parameters involved during water boiling tests. It was demonstrated that the gasifier cookstove would be capable in handling different lignocellulosic biomass materials, although oil palm frond exhibited the highest thermal efficiency.